Administration with L-glutamine and L-glutathione protects the nitrergic innervation of the penile tissue of diabetic rats - Zanoni, Jacqueline Nelisis; Lima, Fabiana Galvão da Motta; Panizzon, Cynthia Priscila do Nascimento Bonato; Trevizan, Aline Rosa; Miranda Neto, Marcílo Hubner de (Acta Scientiarum. Biological Sciences, 2023)
Erectile dysfunction is caused due to neuropathy, resulting from a high oxidative stress, in this way treatment with antioxidants may be promising. Aim of this work was to investigate the effects of the administration of 2% L-glutamine and 1% L-glutathione on the penile tissue of diabetic rats analyzing the nerve fibers that expressing Nitric Oxide Synthase Neuronal (nNOS). Forty-eight male Wistar rats distributed into six groups were used: normoglycemic, diabetic, normoglycemic administered with 2% L-glutamine, normoglycemic administered with 1% L-glutathione, diabetic administered with 2% L-glutamine, and diabetic administered with 1% L-glutathione. After a 120 days experimental period, the animals were euthanized, and the penile tissues were collected and processed for the subsequent immunohistochemical procedure (nNOS) and posterior varicosities morphometry analysis. Diabetic rats administered with L-glutamine and with L-glutathione displayed larger varicosity areas of 14 and 15% compared to the diabetic group (p < 0.05). On the other hand, the administration of 2% L-glutamine and 1% L-glutathione in normoglycemic animals promoted a reduction of 3.3% and 2.4% compared to the normoglycemic group (p < 0.05). We concluded that both L-glutamine and L-glutathione administrations exerted a protective effect on the penile nitrergic innervation of diabetic rats, which can have a positive impact on the erectile function and that their use in normoglycemic animals should be better investigated.